Correction to: Residual Gait Deviations in Children Treated by Medial Open Reduction for Developmental Dysplasia of the Hip at Long-Term Follow-up: A Comparison With Healthy Controls (International Orthopaedics, (2024), 48, 10, (2661-2671), 10.1007/s00264-024-06263-9) - Demirel, Mehmet; EVRENDİLEK, HALENUR; AKALAN, NAZİF EKİN; Bilgili, Fuat; Meriç, Emre; Kuchimov, Shavkat; ÖNERGE, KÜBRA (Springer Nature, 2024)
The correct affiliation of Kübra Önerge should be affiliation 2: Physiotherapy and Rehabilitation Department, Faculty of Health Sciences, İstanbul Kültür University, Istanbul, Turkey. and not affiliation 3. The original article has been corrected. © The Author(s) 2024.
▪️ Residual gait deviations in children treated by medial open reduction for developmental dysplasia of the hip at long-term follow-up: a comparison with healthy controls. International Orthopaedics, Volume 48, Issue 10, Pages 2661 - 2671, October 2024